Optimasi Keseimbangan Lintasan Perakitan Two-Sided Menggunakan Algoritma Simulated Annealing - Riri Damayanti Apnena; Guruh Fajar Shidik (Jurnal TEDC, 2019)
Two-sided line is line series consists of the left side and right are dealing simultaneously. Elements of work to be done the left or right of the transport system (conveyors) and there are also elements of work that can be done on both sides and presented to the assembly of products has a high complexity (eg: product automobiles). Algorithm simulated annealing including the algorithm metaheuristic, ie, an algorithm that allows reception of the solution space larger because considering all the solutions that emerge though not a better solution and take advantage of structural changes occurring in the neighborhood to address issues if the search solution trapped in local minimum. Simulated annealing consists of phase generation solutions initials using the algorithm J-Wagon and stage repair solutions initials in search of local search (exchange and insert).